Pengembangan Sistem Informasi Penjualan Hasil Pertanian Berbasis Web - Amna Amna; Lenawati Asry; Rahmadi Asri; Ratna Dewi; Toni Mahendra (Router : Jurnal Teknik Informatika dan Terapan, 2024)
This research aims to develop a web-based information system that supports the sale of agricultural products in Kampung Bewang. Until now, agricultural product marketing has often been carried out conventionally, limiting market reach and reducing farmers' potential profits. The system is designed to facilitate product management, order tracking, and online payment integration, while also providing a user-friendly interface. The implementation of this system is expected to enhance market accessibility for farmers, expand sales reach, and improve transaction efficiency. Additionally, this system will enable farmers to reduce their reliance on intermediaries, thereby increasing their overall profit.